Dating of sedimentary rock intervals using visual comparison of carbon isotope records: a comment on the recent paper by Bergström et al. concerning the age of the Winneshiek Shale. (16th January 2019) - Lindskog, Anders; Young, Seth A.
Abstract : The recently published Lethaia paper by Bergström et al . (https://doi.org/10.1111/let.12269 ) on the age of the Ordovician Winneshiek Shale (Iowa, USA), and the impact that formed the Decorah crater which hosts this rock unit, is an interesting scientific contribution, although there are a number of problems with the interpretations and data presentation that merit comment. Due mainly to a lack of adequate critical assessment of δ 13 C data and biostratigraphical control, we contend that the conclusions of Bergström et al . are poorly founded and should not be cursorily accepted and propagated in future scientific literature.